2020: A year of uncertainty for South Caucasus states - Georgiana-Cătălina Marcu (CES Working Papers, 2021)
The South Caucasus region has a strategic geopolitical significance due to its importance for energy transports to Europe, but the conflicts, the pandemic and the instability affect people's safety. Moreover, these conflicts are an obstacle to the economic and social development of these countries, and the bilateral and multilateral relations with the West are affected due to influence that Russia has in these countries. In 2020, Azerbaijan seeks new ways for developing economic and commercial linkages with the West and identifies new opportunities for investment, as well as extend cooperation at international level. For Armenia, one of the main goals for 2020 was to identify the best solution for the Nagorny-Karabakh resolution conflict, but things have changed rapidly at the end of September 2020 when the latest Nagorny-Karabakh conflict broke out. Georgia had a lot of protests and social unrest starting with 2019; changing the electoral system was one of the most important requirements for the citizens and after a long period, the Government decide to change the law of electoral system in June 2020. All of these events from South Caucasus and the pandemic also have an important impact on the countries development in the process of establishing new relations with different actors and improving their linkages with the European Union.
Keywords: 330; Black Sea Region; South Caucasus; Eastern Partnership; European Neighbourhood Policy; frozen conflicts